Letter from James Curtis Booth to A. L. Snowden, July 1880 - Booth, James Curtis (1888)
James Curtis Booth (1810-1888) writes to Archibald Loudon Snowden (1835-1912), Superintendent of the Mint of the United States at Philadelphia, to request that the suspension of a skilled worker be reconsidered. Booth notes on the verso, "not submitted."
Keywords: Snowden, Archibald Loudon, 1835-1912; Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States